Pelatihan pendekatan pendidikan karakter holistik guru TK WIKJ GKI elshaday jayapura dalam mengatasi kesulitan belajar peserta didik: - Florida Doloksaribu; Paul Johan Kawatu (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
The Montessori Holistic Approach is an educational approach developed by emphasizing child-centered learning, with a focus on developing the individual potential of children through a structured learning environment and specially designed learning materials. For example, independent learning where children are given the freedom to choose learning materials according to their interests and abilities. This facilitates personal exploration and the development of a sense of responsibility. If in a specially designed environment such as a classroom designed to create a comfortable, safe, and stimulating learning environment. Learning materials are placed in an orderly manner and are easily accessible to children. Based on special learning materials by developingmaterials designed to support exploration and independent learning. These materials are concrete, interactive, and allow children to learn through direct experience. Meanwhile, the role of the teacher as a facilitator is as a facilitator, not as a dominant teacher. Teachers observe and guide children in their learning, providing support as needed. The focus on the development of the Montessori method is not only on academic development, but also on the social, emotional, and physical development of children. Children learn to work together, respect others, and develop independence. As well as absorbing thoughts, children are able to educate themselves, building knowledge through direct experience. The Montessori approach can provide positive benefits for students, namely improving cognitive abilities, such as problem solving and critical thinking, developing independence, self-confidence, and motivation to learn, improving social and emotional abilities, such as cooperation and empathy. So it can be said that the Montessori approach offers a unique and effective educational approach, which focuses on developing the potential of individual children holistically.